2017
DOI: 10.1007/s00040-017-0588-1
|View full text |Cite
|
Sign up to set email alerts
|

Army imposters: diversification of army ant-mimicking beetles with their Eciton hosts

Abstract: Colonies of neotropical army ants of the genus Eciton Latreille offer some of the most captivating examples of intricate interactions between species, with hundreds of associated species already described in colonies of Eciton burchellii Westwood. Among this plethora of species found with Eciton colonies, two genera of staphylinid beetles, Ecitomorpha Wasmann, and Ecitophya Wasmann, have evolved to mimic the appearance and parallel the colouration of the most abundant ant worker cast. Here, we study for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, further taxonomic revisions are required to delimit species and subspecies boundaries. For example, a phylogeographic study based on mitochondrial DNA sequences indicated that genetic divergence of E. burchellii foreli and E. b. parvispinum colonies was higher than between other morphologically described species [51].…”
Section: Eciton Army Antsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, further taxonomic revisions are required to delimit species and subspecies boundaries. For example, a phylogeographic study based on mitochondrial DNA sequences indicated that genetic divergence of E. burchellii foreli and E. b. parvispinum colonies was higher than between other morphologically described species [51].…”
Section: Eciton Army Antsmentioning
confidence: 99%
“…species within the genus Alloiodites [37], to host-specific and only found with colonies of a single Eciton species, e.g. Ecitophya, Ecitomorpha [51]. Some beetles are found in refuse deposits feeding either on dead workers or booty refuse, with reports of flying between bivouacs (e.g.…”
Section: Beetlesmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of mimicry is named Batesian; and mimetic species are highly variable in the degree of their similarity to models (Edmunds 2000 ). Pérez-Espona et al ( 2018 ) studied Ecitomorpha and Ecitophya beetle species which were protected from predation through mimicry (body shape and colour) to the army ant Eciton burchellii . On the other hand, there are some examples when less chemically defended social insects mimic those which are stronger protected.…”
Section: Diversity Of Colour Functions In Social Insectsmentioning
confidence: 99%